Ankle-Brachial Index Is a Powerful Predictor of Renal Outcome and Cardiovascular Events in Patients with Chronic Kidney Disease. (4th January 2012) - Chen, Fu-An; Yang, Chih-Yu; Yang, Wu-Chang; Chen, Jinn-Yang; Ng, Yee-Yung; Li, Szu-Yuan; Liu, Wen-Sheng; Cheng, Shiao-Ti; Wang, Yu-Jen; Lin, Chih-Ching
Abstract : Ankle-brachial index (ABI) is an accurate tool to diagnose peripheral arterial disease. The aim of this study was to evaluate whether ABI is also a good predictor of renal outcome and cardiovascular events in patients with chronic kidney disease (CKD). We enrolled 436 patients with stage 3–5 CKD who had not been undergoing dialysis. Patients were stratified into two groups according to the ABI value with a cut point of 0.9. The composite renal outcome, including doubling of serum creatinine level and commencement of dialysis, and the incidence of cardiovascular events were compared between the two groups. After a median follow-up period of 13 months, the lower ABI group had a poorer composite renal outcome (OR = 2.719, P = 0.015 ) and a higher incidence of cardiovascular events (OR = 3.260, P = 0.001 ). Our findings illustrated that ABI is a powerful predictor of cardiovascular events and renal outcome in patients with CKD.